Hepatoid carcinoma of ovary: a very rare histopathological finding - Wani, Nahida Hassan; Sekhon, Rupinder; Giri, Shevta; Rawal, Sudhir K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Hepatoid carcinoma of the ovary is a rare histopathological variant that has phenotypic properties in common with hepato-cellular carcinoma and composed mainly of epitheloid cells. It presents with unilateral or bilateral ovarian masses with elevated serum α-feta-protein especially in post-menopausal female. We hereby discuss a very rare case of 58 years old female presented with abdominal pain and distension with high serum levels of CA 125 and AFP. She was diagnosed as hepatocellular carcinoma. CT guided FNAC of omentum revealed poorly differentiated carcinoma and on immuno-histochemical staining cells was positive for CK7, CK8/17 and AFP. The tumor cells were negative for CMA, PAX2/PAX8, CK20 and CK19. She was diagnosed with bilateral hepatoid carcinoma of ovary. This shows that histopathological examination and tissue immuno-histochemical staining plays an important role in distinguishing hepatoid variety of ovarian carcinoma from other ovarian tumors and hepatocellular carcinoma.